The Impact of Calcium Carbonate on the Bulk Density of selected Libyan Calcareous Soils in Al Jabal Al Al-kdhar Region - Habel, Ahmed Y.; Abdalgader, Kamal A.; Aldifry, Atia E. (Al-Mukhtar Journal of Sciences, 2015)
There are few scientific journals that tackle in detailed studies concerning the effect of calcium carbonate on the soil bulk density and therefore on other related physical properties to it, such as soil aeration, available water capacity, and other characteristics that can have a significant role in agricultural production processes.Most of researchers in the field of soil science pointed out that bulk density are affected by the mineral components of soil (sand, silt, and clay) and organic matter content. As a result of the prevailed climatic conditions in Libya; scarcity in rainfall and high temperature, making these soils poor in both organic matter and clay contents, as well as rich in the proportion of calcium carbonate. Based on the foregoing facts, the present work aims to study the interrelationships between bulk density and those components. To achieve this purpose, a thirty eight soil samples were collected at a depth ranges from 5 to 10 cm from Aziat area, south of Jabal Al Alkdhar Region. Correlation coefficients confirmed that there was a proportional correlation between the values ​​of bulk density and soil content of sand and calcium carbonate (0.864, 0.902), while this was an inversely related with each of the percentage of silt, clay and organic content (0.800, 0.705, 0.426). On the other hand the regression equations confirmed that calcium carbonate has the greater role in determining the bulk density and total porosity and thus water holding capacity of soils.